Proceedings of the 2017 International Conference on Management, Education and Social Science (ICMESS 2017) 2017
DOI: 10.2991/icmess-17.2017.39
|View full text |Cite
|
Sign up to set email alerts
|

Transforming Needs and Countermeasures of Old Communities-A Case Study of Dalian in Liaoning Province

Abstract: Abstract-According to the appropriate dimensions offered by World Health Organization (WHO) and American Association of Retired Persons (AARP), this paper make the transforming need dimensions for old communities in Dalian, China. And we carry out a survey in 50 communities in Dalian, covering four districts and high-tech zone, whose data are then analyzed by a structural equation model. This allows us analyzing empirically the effect of the shortage in aging service in Dalian, so the communities can meet the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Through in-depth participation to provide residents with a voice channel, in order to meet their desire to participate in community management, we can create an inclusive and shared community environment, and promote grassroots social governance. From the perspective of case study, Fan X. et al [26] used the example of 50 communities in Dalian to conduct an empirical analysis. The results showed that the transforming needs of old communities include accessibility, building and housing, community care and activities, and spiritual needs.…”
Section: Plos Onementioning
confidence: 99%
“…Through in-depth participation to provide residents with a voice channel, in order to meet their desire to participate in community management, we can create an inclusive and shared community environment, and promote grassroots social governance. From the perspective of case study, Fan X. et al [26] used the example of 50 communities in Dalian to conduct an empirical analysis. The results showed that the transforming needs of old communities include accessibility, building and housing, community care and activities, and spiritual needs.…”
Section: Plos Onementioning
confidence: 99%
“…The contradiction between the proliferation of the number of elderly people and the construction of local infrastructure and service is also becoming increasingly evident. Existing community living spaces are no longer able to meet the growing needs of older people, and the environment and social services constructed without an all-ages inclusive perspective have caused many inconveniences to older people's lives (Fan et al, 2017;Guo & Pan, 2013;Hu, 2020;Wang & He, 2021). Therefore, the need for age-friendly transitions in communities and spaces becomes urgent, and the systematic and sustainable nature of the transition approach becomes a key factor in measuring the success of the transition.…”
Section: Introductionmentioning
confidence: 99%